Neuropilin‐1 is required for endothelial cell adhesion to soluble vascular endothelial growth factor receptor 1. (27th August 2021) - Colotti, Gianni; Failla, Cristina Maria; Lacal, Pedro Miguel; Ungarelli, Mariangela; Ruffini, Federica; Di Micco, Patrizio; Orecchia, Angela; Morea, Veronica
Abstract : Neuropilin‐1 (NRP‐1) is a semaphorin receptor involved in neuron guidance, and a co‐receptor for selected isoforms of the vascular endothelial growth factor (VEGF) family. NRP‐1 binding to several VEGF‐A isoforms promotes growth factor interaction with VEGF receptor (VEGFR)‐2, increasing receptor phosphorylation. Additionally, NRP‐1 directly interacts with VEGFR‐1, but this interaction competes with NRP‐1 binding to VEGF‐A165 and does not enhance VEGFR‐1 activation. In this work, we investigated in detail the role of NRP‐1 interaction with the soluble isoform of VEGFR‐1 (sVEGFR‐1) in angiogenesis. sVEGFR‐1 acts both as a decoy receptor for VEGFs and as an extracellular matrix protein directly binding to α5β1 integrin on endothelial cells. By combining cell adhesion assays and surface plasmon resonance experiments on purified proteins, we found that sVEGFR‐1/NRP‐1 interaction is required both for α5β1 integrin binding to sVEGFR‐1 and for endothelial cell adhesion to a sVEGFR‐1‐containing matrix. We also found that a previously reported anti‐angiogenic peptide (Flt2‐11 ), which maps in the second VEGFR‐1 Ig‐like domain, specifically binds NRP‐1 and inhibits NRP‐1/sVEGFR‐1 interaction, a process that likely contributes to its anti‐angiogenic activity. In view of potential translational applications, we developed a five‐residue‐long peptide, derived from Flt2‐11, which has the same ability as the parent Flt2‐11 peptide to inhibit cell adhesion to, and migration towards, sVEGFR‐1. Therefore, the Flt2‐5 peptide represents a potential anti‐angiogenic compound per se, as well as an attractive lead for the development of novel angiogenesis inhibitors acting with a different mechanism with respect to currently used therapeutics, which interfere with VEGF‐A165 binding. Abstract : Endothelial cell adhesion to sVEGFR‐1, which is mediated by the α5β1 integrin/sVEGFR‐1 interaction, requires neuropilin‐1. Neuropilin‐1 interacts with both α5β1 integrin (on the same cell membrane) and sVEGFR‐1 (in the extracellular matrix) with high affinity, likely stabilizing the α5β1 integrin/sVEGFR‐1 interaction. Peptides Flt2‐11, Flt2‐8 and Flt2‐5, which are able to inhibit neuropilin‐1/sVEGFR‐1 interaction, have anti‐angiogenic activity that might be exploited for therapeutic purposes.